Reflections on the past and future of language testing and assessment: An emerging scholar's perspective. (January 2023) - Burton, J. Dylan
In its 40th year, Language Testing journal has served as the flagship journal for scholars, researchers, and practitioners in the field of language testing and assessment. This viewpoint piece, written from the perspective of an emerging scholar, discusses two possible future trends based on evidence going back to the very first issue of this journal. First, this paper outlines past efforts to describe and define the construct of second language communication, noting that much work has yet to be done for a more complete description in terms of interactional competence and nonverbal behavior. The second trend highlights the growing movement in applied linguistics toward research transparency through Open Science practices, including replication studies, the sharing of data and materials, and preregistration. This paper outlines work to date in Language Testing that encourages open practices and emphasizes the importance of these practices in assessment research.